Population control as a human right : international law and the global quest to curb overpopulation / Roman Birke. - Birke, Roman (Human rights in history., 2025)
Concerns about global overpopulation spread rapidly in the 1940s and still persist today. The UN Resolution on Human Rights and Family Planning (1968) provided justifications for the argument that population growth endangered the realization of human rights and codified a right to contraception to halt this growth. Conversely, human rights were also invoked on the other side of this debate, with family planning regarded as an essential individual right independent of demographic considerations. Roman Birke explores how human rights became central to this debate, utilised by international actors including NGOs, the women's movement, international lawyers, and institutions such as the United Nations. He analyses how couples' intimate choices related to domestic and international policy, and how this varied across the world, through case studies of India, Ireland, the USA, and Yugoslavia. This is an essential contribution to the evolving literature on the role of reproductive politics in global political landscapes.